Influence of the nature of pro-oxidants on the photooxidation of polyethylene blown films - João Augusto Osório Brandão; Fernando dal Pont Morisso; Edson Luiz Francisquetti; Ruth Marlene Campomanes Santana (Heliyon, 2022)
In an attempt to reduce the accumulation of polymeric waste in the environment, such as plastic bags, the use of pro-oxidants has been adopted in polyolefins, including polyethylene (PE), which is one of the most used polymers in film production. The incorporation of this additive to PE film aims to accelerate its oxidation in the process of abiotic degradation, generating oxygenated groups that can facilitate the biotic degradation. Commercial pro-oxidants are commonly organic salts of transition metals. However, their use can lead to a secondary problem, the inappropriate accumulation of transition metals at the site where the polymeric waste was deposited and, for this reason, it has been sought pro-oxidants metals free and that can also be biodegraded. In this context, this work aimed to evaluate the photodegradation of PE blown films obtained by extrusion using a commercial pro-oxidant, d2w™, an alternative organic pro-oxidant, benzoin, and also a standard film, without pro-oxidant. After undergoing 96 and 144 h of UV light exposure, the blown films were evaluated by dilute solution viscometry, FTIR and SEM analysis. The results showed that the pro-oxidants lead to the formation of more macromolecular fragments containing carbonyl groups than in the standard PE film. The film extruded with benzoin showed greater fragmentation, which may be associated with a greater reduction in the average viscosimetric molar mass, therefore, this additive being a promising organic substance in the induction of photooxidation, as demonstrated by the other results obtained by FTIR and SEM.